PENILAIAN PERGERAKAN MASSA TANAH BERDASARKAN ZONASI DI WISATA TERPADU BUKIT TETEMPANGAN KECAMATAN MANDOLANG KABUPATEN MINAHASA - Hidania Leony Chirsty; Zetly E. Tamod; Karamoy L. Theffie (Universitas Sam Ratulangi, 2018)
ABSTRACT Mass movement is often called landslide is an one product from equilibrium slope distruption that can make mass movement dan rocks to another place.Â This research is to know the steps of landslide sensitivity on Tetempangan Hill at Koha and Mokupa, Minahasa Regency during sixth month start from November 2017 until May 2018.Â This research use scoring method devided two variable of landslide sensitivity that is natural physical aspect and human activity aspect refer to Peraturan Menteri Pekerjaan Umum Nomor 22 tahun 2007 and the processing by using Geography Information System in this case Arcgis 10.3 to obtain the scope area and landslide sensitivity map along with Global Mapper 19th Software to make the cross section.Â The result of this research show that the steps of potentially zone landslide sensitivity at Tetempangan Hill is in medium sensitivity category at Type Zone A and Type Zone B with each scope area 14,87 Ha and 16,46 Ha. Key words : Sensitivity, landslide, Geography Information System